Comparison of Magnetic Resonance Imaging and Contrast-Enhanced Ultrasound as Diagnostic Options for Unclear Cystic Renal Lesions: A Cost-Effectiveness Analysis - Gassert, Felix; Schnitzer, Moritz; Kim, Su Hwan; Kunz, Wolfgang G.; Ernst, Benjamin Philipp; Clevert, Dirk-André; Nörenberg, Dominik; Rübenthaler, Johannes; Froelich, Matthias Frank (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose Correct differentiation between malignant and benign incidentally found cystic renal lesions has critical implications for patient management. In several studies contrast-enhanced ultrasound (CEUS) showed higher sensitivity with respect to the accurate characterization of these lesions compared to MRI, but the cost-effectiveness of CEUS has yet to be investigated. The aim of this study was to analyze the cost-effectiveness of CEUS as an alternative imaging method to MRI for the characterization of incidentally found cystic renal lesions.Materials and Methods A decision model including the diagnostic modalities MRI and CEUS was created based on Markov simulations estimating lifetime costs and quality-adjusted life years (QALYs). The recent literature was reviewed to obtain model input parameters. The deterministic sensitivity of diagnostic parameters and costs was determined and probabilistic sensitivity analysis using Monte-Carlo Modelling was applied. Willingness-to-pay (WTP) was assumed to be $ 100 000/QALY.Results In the base-case scenario, the total costs for CEUS were $9654.43, whereas the total costs for MRI were $9675.03. CEUS resulted in an expected effectiveness of 8.06 QALYs versus 8.06 QALYs for MRI. Therefore, from an economic point of view, CEUS was identified as an adequate diagnostic alternative to MRI. Sensitivity analysis showed that results may vary if CEUS costs increase or those of MRI decrease.Conclusion Based on the results of the analysis, the use of CEUS was identified as a cost-effective diagnostic strategy for the characterization of incidentally found cystic renal lesions.
Keywords: ultrasound; contrast-enhanced ultrasound; cost effectiveness; renal lesions; magnetic resonance imaging